HAMBATAN TURKI UNTUK MENJADI ANGGOTA UNI EROPA PADA MASA PRESIDEN ERDOGAN - Sarah Khairiyah Nasution; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Over the decades, The relationship between Turkey and European Union has been marked with many agreements and convergentions, in shape of economic, cultural, and social life exchanges which are rooted between The Ottoman Empire and European’s power. Turkey has become one of a countries as well as partner that has an important role for the European Union, or vise versa. The process of Turkey’s bid to become part of the European Union has been going on for a long time. Since 1963, Turkey has participated in the regional integration of the European Economic Community, which is now a pioneer of European Union shaping. Turkey has made many policy changes in its country to fulfill the criterias given by the European Union. In examining this phenomenon, the author uses Neorealism perspective. Neorealism sees that it is natural for the European Union to hinder Turkey’s efforts to become part of its organization, because the European Union has its own interests in maintaining its internal security and identity. The theory used to support this research is The Complex Regional Security Theory. This theory emphasizes that there are boundaries made by the European Union outside of itself, so that even though the European Union has cooperated with Turkey, there is no mixing of identity which requires the European Union to accept Turkey as its member. Through this research, the author formulate, the hurdles that Turkey experiences to become the member of European Union are divided into four different fields, namely politics and security, economy, human rights and democracy, and socio-culture. Until now, Turkey’s effort to be accepted as the member of European Union have often met with stalemates and rejection from European Union heads of state. Keywords: Turkey, European Union, Hurdles